Estimation on incidence of all-cause otitis media among under-5 children in Suzhou, 2017 - 2020 - Wanjing LIN; Qinghui CHEN; Chen QIAN; Zhaojin LI; Jun ZHU; Genming ZHAO; Jianmei TIAN; Tao ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
Objective To estimate the incidence of all-cause otitis media (OM) in children under 5 years old (under-5) in Suzhou city, Jiangsu province. Methods From the Health Information System (HIS) of Soochow University Affiliated Children's Hospital (SCH), we extracted outpatient visit and hospitalization records of local under-5 children (born from 2017 to the end of 2020) during the period from January 2017 through June 2021 for a retrospective cohort analysis. The children with the diagnosis of all-cause otitis media were followed up for the estimation of overall and age specific all-cause otitis media incidence among the children. ResultsAmong the 507 678 children followed-up during the 4-year period, 9 378 otitis media incidents of 7 903 children were identified, including 8 979 outpatient incidents and 399 hospitalizations. The overall incidence rate of otitis media was 6.37/1 000 person-years and the incidence rate was 6.10/1 000 person-years for outpatient children and 0.27/1 000 person-years for inpatient children, respectively. The incidence rate of otitis media was higher among the children aged 3 - 4.5 years and the highest incidence rate of 24.59/1 000 person-years was observed in the children aged 4 - 4.5 years. Higher otitis media incidence rate of 21.45/1 000 person-years was also observed for the children with allergic rhinitis and recurrent acute upper respiratory infections. Conclusion The incidence rate of all-cause otitis media was low and influenced by age and other diseases among under-5 children in Suzhou city.